Pengaruh Kejadian Tetralogy of Fallot pada Anak dengan Riwayat Diabetes Mellitus Tipe II dengan Labiopalatochiszis - Afif Ferdian; R. Mohamad Javier; Himawan Wicaksono; Budi Prakoso; Ananingati Ananingati; Akhmad Rusli Budi Ansyah (Syntax Idea)
There is a suspicion that the condition of the cleft lip and palate has something to do with labiopalatochiszis with COL1A2 heterozygous mutations and DNA formation accompanied by Tetralogy of Fallot in children and history of type II diabetes mellitus in mothers. Then, it is also found in infants with labiopalatochiszis usually accompanied by frequent occurrences of TOF due to the genetic influence of the event. This has led to speculation that there are links between the above variables and cleft lip and palate. Therefore, this study tries to find the relationship between these variables. Objective: Determine the effect of tetralogy of fallot events on children with a history of type II diabetes mellitus and Labiopalatochiszis. This research is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method or commonly called PRISMA, this method is carried out systematically by following the correct research stages or protocols. Sources taken from the Google Scholar site with journals published in 2017-2023 and then screened 1,870 journals. Journal clustering was carried out and obtained the number of journals indexed Q1 amounting to 4 journals, Q3 amounting to 1 journal, and Q4 amounting to 1 journal so that there were 6 journals extracted. The entire journal does not discuss directly the relationship between research variables, but only provides an overview of the influence that TOF occurs on mothers with type 2 diabetes mellitus conditions and the occurrence of labiopalatochiszis.